2022
DOI: 10.48550/arxiv.2201.11416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theory of Electron Injection at Oblique Shock of Finite Thickness

Takanobu Amano,
Masahiro Hoshino

Abstract: A theory of electron injection into diffusive shock acceleration (DSA) for the generation of cosmic-ray electrons at collisionless shocks is presented. We consider a recently proposed particle acceleration mechanism called stochastic shock drift acceleration (SSDA). We find that SSDA may be understood as a diffusive particle acceleration mechanism at an oblique shock of finite thickness. More specifically, it is described by a solution to the diffusion-convection equation for particles with the characteristic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Early 1D PIC simulations 15,16 demonstrated that at these shocks the escaping (also called reflected) electrons streaming along the oblique magnetic field are capable of exciting various electro-static and electromagnetic instabilities. This regime is particularly interesting due to very efficient electron acceleration found in oblique shocks, namely stochastic shock-drift acceleration [18][19][20] . However the foreshock structure and the long-term evolution are poorly understood in shocks with θ Bn = 60 • and we use 2D PIC simulation to address these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Early 1D PIC simulations 15,16 demonstrated that at these shocks the escaping (also called reflected) electrons streaming along the oblique magnetic field are capable of exciting various electro-static and electromagnetic instabilities. This regime is particularly interesting due to very efficient electron acceleration found in oblique shocks, namely stochastic shock-drift acceleration [18][19][20] . However the foreshock structure and the long-term evolution are poorly understood in shocks with θ Bn = 60 • and we use 2D PIC simulation to address these issues.…”
Section: Introductionmentioning
confidence: 99%